The Role of Humans as Objects and Subjects in Education: Basic Understanding and Implementation - Najwa Nailah Salsabila; Hafidz; Ence Raisha Renaldi; Olyvia Nanda Armila; Lailatul Hanifah; Rafa Hanif Maulida; Anugerah Gelora Saputra; Muhammad Gibran Naufali (Bulletin of Islamic Research, 2025)
In human life, he plays the role of a subject as well as an object. This also applies in the world of education, where humans hold a role as the subject and object of education. The topic of Humans as Objects and Subjects of Education leads readers to understand that humans play both roles. Thus, readers are expected to understand the basic understanding of human beings, the nature of human beings, and how human beings function as objects and subjects in education. This understanding begins with a general concept of human beings. Readers are invited to think about how humans play the role of educational objects and subjects who, in daily life, are directly involved in various educational activities. Therefore, there is no reason not to study the role of humans in such contexts. Furthermore, readers are invited to think and discuss further about the meaning of humans, the role of humans as objects of education, and the role of humans as educational subjects.